PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT.ANTAR SURYA JAYA SURABAYA - Nuzulul Fatimah; Priyono Priyono (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2016)
This study aims to determine the effect of the work environment, job satisfaction, motivation, and discipline the performance of employees at PT. Antar Surya Jaya Surabaya. This research was conducted using a quantitative approach is, research that focuses on testing the hypothesis with statistical methods of analysis measuring devices and produce results that can be generalized. The research instrument a questionnaire. Samples are employees of PT. Antar Surya Jaya Surabaya. The population in this study are employees of PT. Antar Surya Jaya Surabaya as many as 150 employees. Samples taken in this study were 60 respondents who are determined based on the formula Slovin. The sampling technique in this research using random sampling. Test equipment used is the technique of multiple linear regression analysis with SPSS software 16. According to a study obtained by multiple linear regression equation is Y = 8.010+ 0.214X1 + 0.039X2 + 0.072X3 + 0.227X4. And the value of F test shows Fhitung 6898> Ftable 2:54 with significant value 0.000 <0:50, which means variable Work Environment, Job Satisfaction, Motivation and Work Discipline simultaneously affect employee performance. The results of the t test variable Work Environment worth thitung 2200> ttabel 2.00404 with significant value 0.032 <0.05 variables Job Satisfaction worth thitung 0286 <ttabel 2.00404 with significant value 0776> 0.05, variable Motivation worth thitung 0.681 <ttabel 2.00404 with significant value 0499> 0.05, Work Discipline variable worth thitung 2328> ttabel 2.00404 with significant value 0.024 <0.05 which means that the variable Work Environment and Work Discipline positive and significant impact on employee performance, whereas for Job Satisfaction and Motivation variable positive but not significant effect on employee performance. And in this study, it turns out the variables that most influence Work Discipline Employee Performance.